2014
DOI: 10.1111/aji.12327
|View full text |Cite
|
Sign up to set email alerts
|

Placenta Growth Factor Induces Invasion and Activates p70 during Rapamycin Treatment in Trophoblast Cells

Abstract: We conclude that first trimester trophoblast invasion is functionally decreased when phosphorylation of mTOR is prevented and this decrease is recovered with the addition of PlGF. Mechanistically, this recovery involves the phosphorylation of p70 independent of mTOR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 36 publications
3
32
0
Order By: Relevance
“…It has been shown that inhibiting the phosphorylation of mTOR down-regulated the PlGF mRNA level (PlGF, a member of the VEGF family proteins) [41]. In agreement with previous study, the relative mRNA level of VEGF-A in placenta was increased by COS supplementing.…”
Section: Discussionsupporting
confidence: 89%
“…It has been shown that inhibiting the phosphorylation of mTOR down-regulated the PlGF mRNA level (PlGF, a member of the VEGF family proteins) [41]. In agreement with previous study, the relative mRNA level of VEGF-A in placenta was increased by COS supplementing.…”
Section: Discussionsupporting
confidence: 89%
“…In addition, PIGF is a secreted proangiogenic protein that belongs to the VEGF family. PIGF participates in the development of the intrauterine vascular network, trophoblast invasion, and inflammatory processes [ 43 ]. Decreased maternal serum levels of PIGF during early gestation correlate with an increasing risk of abnormal pregnancy and, specifically, early-onset preeclampsia [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…The importance of the JZ is underscored by the previous observation that decreased trophoblast invasion is observed when mTOR activation is inhibited (Knuth et al. ). We therefore conclude that IUGR is correlated with increased 4EBP1 activity in the invading trophoblast cells of the uterine mesometrial compartment, decreased activation of the mTOR protein, and decreased trophoblast invasion in the placenta during maternal hypoxia‐induced IUGR.…”
Section: Discussionmentioning
confidence: 99%
“…Such differential responses suggest alternative mechanisms for these proteins in the placenta during IUGR that has not yet been adequately defined. Our laboratory has shown a direct correlation between mTOR protein activation and trophoblast invasion, suggesting a central role for this pathway in the regulation of trophoblast invasion during IUGR (Knuth et al 2014). We hypothesized that maternal hypoxia will induce IUGR by regulating proteins associated with the mTOR pathway.…”
Section: Introductionmentioning
confidence: 99%